Local-Thinking Bias - deHaan, Ed; Lee, Charles M. C.; Loh, Wei Ting (The Accounting Review, 2025)
ABSTRACT Local-thinking bias, wherein agents overweight information that comes readily to mind, is a prominent finding in cognitive psychology. In this study, we investigate local-thinking bias in the context of sell-side analysts and measure each analyst’s “local” information as news stemming from their individual coverage portfolio. Tests examining multiple analysts forecasting on the same focal firm at the same time find that individual analysts overweight idiosyncratic local news and underweight news from economically linked firms that are not in their coverage portfolios. Market prices track the analyst bias from local news, leading to predictable and economically significant return reversal patterns in the future. A trading strategy that adjusts for analysts’ biases earns meaningful abnormal returns. We discuss the implications of these findings for three literatures: (1) cognitive psychology, (2) analyst behavior, and (3) behavioral asset pricing. JEL Classifications: D91; G14; G17; G41; M41; M49.